Leal da Câmara y Valle-Inclán: un testimonio epistolar sobre sendos lances de honor en 1899 - González Martel, Juan Manuel (Madrygal. Revista de Estudios Gallegos, 2009)
Tomás Julio Leal da Câmara (1876-1948), Portuguese painter and cartoonist, was the leading role of an event that happened during his time in Madrid from 1890 to 1900. This event, that became a reknown incident in the Spanish literary world, was the verbal and physical confrontation between the writers Ramón María del Valle- Inclán and Manuel Bueno, that took place in a café. The young Portuguese artist, author of one of the most famous caricatures of Don Ramón, would tell about his own honor question in a personal letter, another political argument with a challenge to a duel that would indirectly lead to the fatal incident between Bueno and Valle-Inclán.
Keywords: Valle-Inclán; Leal da Câmara; Bueno; Portuguese artist; Caricature